Development Instrument Penelitian Peran Serta Ibu hamil dalam Upaya Ayah Berhenti Merokok untuk Pencegahan Stunting melalui Pendekatan Model Kepercayaan Kesehatan: Uji Validitas dan Reliabilitas - Nur Rohmah; Maya marinda; Ike Anggraeni (Journal of Health, 2025)
Indonesia has the largest number of smokers in the world, ranking third after India and China. Pregnant women have an important role as they are caregivers and can influence their husbands to quit smoking. Indonesia has the third largest number of smokers in the world, with 33.5% of the Indonesian population smoking, posing health risks. Family support is needed in smoking cessation efforts, especially for fathers or husbands. The purpose of this study was to conduct a reliability test analysis and establish validity must be done to ensure the instrument provides accurate and consistent results. This research design is a cross-sectional survey study or data collection at one time to test the validity and reliability of the research questionnaire with the title Participation of Pregnant Mothers in the Efforts of Fathers to Stop Smoking to Prevent Stunting through the Health Belief Model Approach. The validity-reliability study was conducted on pregnant women at the Palaran Community Health Center in Samarinda City, Indonesia, which was conducted in September 2024 in a group of pregnant women who had smoking husbands as many as 30 respondents. The findings of this study revealed that the validity values obtained varied between a minumum of 0.001 and a maximum of 0.97. In addition, the reliability of the seven variables was assessed using Cronbach's alpa coefficient, which yielded values above 0.7. Therefore, this tool can be a valuable tool to measure the participation behavior of pregnant women in efforts to help their husbands stop smoking for stunting prevention.